Accenture/Ponemon Institute: The Cost of Cybercrime. Issue 3 (March 2019) - Unknown
Abstract : Now in its ninth year, this annual report never makes for comfortable reading. The numbers it places on the consequences to businesses of falling victim to cybercrime are simply eye-watering. And while Accenture, the sponsor of this year's report, tries to put a positive spin on the issue, the overall message is that things are getting worse.